Monitoring the positioning of short polycationic peptides in model lipid bilayers by combining hydrogen/deuterium exchange and electrospray ionization mass spectrometry - de Souza, Bibiana Monson; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2008)
Electrospray ionization mass spectrometry (ESI-MS) was used to analyze the hydrogen/deuterium exchange properties of the mastoparan peptide Apoica-MP during interactions with lipid vesicle membranes. Synthetic peptide was incorporated into large unilamellar vesicles (LUVs) of L-alpha-phosphatidylcholine (PC), resulting in proteoliposomes which were then diluted with D(2)O. After quenching deuteration by the addition of formic acid the H/D exchange was directly analyzed by ESI-MS. This strategy was used to investigate the architecture of the peptide in the membranes of PC LUVs. The deuterated peptide ions were analyzed under collision-induced dissociation (CID) mass spectrometry, which permitted the location of deuterons at the amide sites along the peptide backbone. Intramolecular hydrogen scrambling was investigated both in the free peptide and in its proteoliposome form. Some scrambling was observed for the free peptide; however, almost no scrambling occurred in the amide hydrogens of the peptide backbone embedded in the membrane. The CID spectra suggest that the N-terminal moiety of the peptide lies on the polar side of the lipid membrane, while the C-terminal region is embedded in the membrane. The protocol described here may be reliably applied to investigate the interaction of mastoparans with bilayer lipid systems. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Proteoliposome; Mass spectrometry; Peptide sequencing; Anti-microbial peptide; Deuterium scrambling; Peptide-membrane interaction